Fibra de cana-de-açúcar na alimentação de leitões recém-desmamados - Silva Guillen, Ysenia Victoria [UNESP] (2014)
Were evaluated the effects of sugarcane fiber inclusion in the diets of weanling piglets on performance, incidence of diarrhea, gastrointestinal transit time, digestive organs weight, and morphophysiological and microbiological traits of the gastrointestinal tract. Ninety-six barrows weaned at 21 days of age and initial body weight of 6.67 ± 0.63 kg were used in a randomized complete block design with four treatments, eight replicates per treatment and three pigs per experimental unit. Dietary treatments consisted of 0, 1, 2, or 3% sugarcane fiber inclusion. At 35 days of age, one animal (final body weight of 8.24 ± 0.63 kg) per experimental unit was slaughtered to evaluate organs weight (stomach, small intestine, cecum, and colon) and intestinal histology (villus height, crypt depth, villus-to-crypt ratio, number of goblet cells and villus density). Digesta samples from the small intestine, cecum, and colon were collected to measure pH and viscosity. Short-chain fatty acids concentrations (acetic, propionic, and butyric acids) were determined in digesta samples from the small intestine and cecum. Lactobacillus spp., Escherichia coli, and Clostridium perfringens counts were determined in digesta samples from the small intestine. From 21 at 35 days of age, average daily gain (P = 0.009) and average daily feed intake (P = 0.014) increased linearly with the increasing sugarcane fiber levels. Although the treatments did not affect (P > 0.05) gastrointestinal transit time, incidence of diarrhea, pH, viscosity, organs weight, and intestinal microbiology, there was a linear increase in cecal propionic (P = 0.006) and butyric (P < 0.01) acids concentrations with increasing sugarcane fiber inclusions. Increasing dietary sugarcane fiber levels resulted in a linear decrease (P = 0.003) in duodenal villus-to-crypt ratio and in a linear increase (P = 0.028) in crypt depth in the jejunum. In conclusion, adding up to 3% of sugarcane fiber to the ...